Caste/ethnic differences in school dropout among 5-20-year olds in Nepal. Issue 4 (7th June 2022) - Devkota, Satis; Eklund, Jesse; Wagle, Udaya
ABSTRACT: Reducing school dropout rates has been a challenging policy problem in an effort to improve educational participation and attainment in developing countries. This paper examines the differences in school dropout rates among the 5–20-year olds across three major caste/ethnic groups in Nepal using nationally representative survey data. Findings suggest sizeable differences witnessed by the indigenous and especially lower-caste Dalit groups when compared to the historically privileged Hindu groups. The use of Fairlie's non-linear regression-based decomposition technique helps ascertain the major sources of these differences. Parental occupations, age, marital status and mountains, hills and far-western regions of residence are found to help explain such differences. The paper underscores the role of public policies on affirmative action and area-based, conditional cash transfer initiatives as well as effective public awareness campaigns to improve the educational participation of these otherwise historically disadvantaged caste/ethnic groups in Nepal.